Identification and Genetic Diversity Analysis of Cucurbita Varieties Based on SSR Markers - Jialong Zou; Xingting Wu; Xuejing Liu; Changcheng Peng; Yingxue Ma; Xiujie Zhang; Xuhong Yang; Shuailong Luo; Weigeng Xing; Hao Hong; Lang Li; Bin Tan; et al. (Agronomy, 2025)
Cucurbita L. is a valuable gourd vegetable crop, with high nutritional and economic value. However, the lack of a molecular identification system and population genetic information has impeded the development of proper conservation strategies and marker-assisted genetic breeding for Cucurbita varieties. In this study, we developed a set of simple sequence repeat (SSR) markers for distinguishing the main cultivated Cucurbita cultivars in China and providing technical support for domestic variety preservation, registration, and intellectual property protection. A total of 152 allelic variations and 308 genotypes were identified from 306 Cucurbita cultivars by using 24 SSR markers. Using 24 core markers, we successfully distinguished 300 varieties from 306 Cucurbita varieties, and the identification rate reached 98.36%. The PIC values of the 24 core markers ranged from 0.281 to 0.749, and the average value was 0.643, which was considered high genetic diversity. Based on the results of cluster analysis, principal component analysis, and population genetic structure analysis using 24 pairs of core primers for 306 Cucurbita varieties, the results were basically consistent, all categorized into three genetic clusters, corresponding to the three species: C. moschata, C. pepo, and C. maxima. These results showed a certain correlation with phenotypic traits. DNA fingerprints were constructed for the 306 Cucurbita cultivars based on the core markers. Our research results provide a new tool for population genetic analysis, variety identification, and protection in Cucurbita cultivars with high efficiency, accuracy, and lower costs compared to conventional methods.